The effect of the problem-based learning model assisted by pop-up books on the critical thinking skills of fourth grade students in the IPAS subject - Khasanah, Widya Miftahul; Wulandari, Heny; Ningrum, Ayu Reza (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model assisted by pop-up book media on the critical thinking skills of fourth-grade students in the IPAS subject. The research employed a quantitative approach using a quasi-experimental design with a posttest-only control group design. The sample consisted of two classes: the experimental group, which used the PBL model with pop-up book assistance, and the control group, which used the cooperative Think Pair Share method. The research instrument was a multiple-choice test based on indicators of critical thinking skills. The data analysis revealed a significant difference in posttest scores between experimental and control groups. The experimental group achieved higher learning outcomes, indicating that the combination of PBL and visual media such as pop-up books effectively enhances students’ critical thinking skills. The novelty of this research lies in the integration of a problem-based learning model and visual media in IPAS instruction, particularly for fourth-grade students who had never used such media before. This approach has proven to encourage active student engagement and provide a more enjoyable and meaningful learning experience.